PENGARUH SOCIAL MEDIA MARKETING ACTIVITIES DAN CUSTOMER KNOWLEDGE TERHADAP VISIT INTENTION DIMEDIASI OLEH PERCEIVED VALUE - Iriadi, Felicia Winona; Achmadi, Hendra (FEB Universitas Sam Ratulangi Manado, 2024)
The growth in the number of clinics in developing countries has caused an oversaturation and a competitive environment. However, while some clinics are seen thriving, others are left behind in the competition. Therefore, a new breakthrough of marketing strategies is needed to unlock the secret to keep up with the competition. The purpose of this study is to analyze the influence of social media marketing and customer knowledge to visit intention with perceived value as a mediation variable. Sample data for this research was taken using non-probability sampling method with questionnaires from individuals who had seen the social media of Bianca Aesthetic Clinic. There are 320 samples that met the requirements and was analyzed with PLS-SEM. The results showed that five of the six independent variables were proven to have a significant and positive effect. Interactivity on social media is proven to have the most powerful influence, followed by informativeness, trendiness, customer knowledge, and electronic-Word of Mouth (e-WOM). The findings of this study prove the positive impact of perceived value on visit intention. Suggestion for further research is that new variables must be taken into account to narrow the limitations in this research.